DAMPAK SOCIAL CAPITAL DAN ENTREPRENEURIAL ORIENTATION PADA INNOVATION CAPABILITIES DALAM KONTEKS UMKM - Elistia; Dedi Purwana; Usep Suhud; Tuty Sariwulan (Journal of Innovation Research and Knowledge, 2022)
The innovation capabilities of Micro, Small and Medium Enterprises (MSMEs) are very important to enhance the competitive advantage and performance of the business. The aim of the research is to analysis the effect of Social Capital (SC) and Entrepreneurial Orientation (EO) on Innovation Capabilities (In). This research is a descriptive study by applying a quantitative methodology to analyses the significance of the factors that affect Innovation Capabilities using simple random sampling technique on 86 respondents of culinary MSMEs located in DKI Jakarta, Indonesia. Data processing and analysis was carried out using SMART PLS. The results of hypothesis testing indicate that Entrepreneurial Orientation (EO) have a positive and significant effect on Innovation Capabilities (In), but Social Capital (SC) is not significant. Therefore, further research will conduct research model that makes SC as an indirect variable and develop a research model framework for other factors that have an impact on Innovation Capability and Business Performance.